Description of HIV/AIDS Incidence in Helvetia Health Center, Medan City - Apriliani Apriliani; Rahmat Alyakin Dachi; Mido Ester Juniati Sitorus; Donal Nababan; Siska Evi Simanjuntak (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
HIV/AIDS is a contagious disease that has become a strategic issue in the SDGs (Sustainable Development Goals) agenda, making it a priority for development in every country to achieve HIV/AIDS elimination by 2030. HIV/AIDS poses a significant challenge to public health globally, affecting both developed and developing countries, including Indonesia. This study aims to provide an overview of the incidence of HIV/AIDS at Puskesmas Helvetia. The study employed a quantitative design with a case-control approach. The research was conducted at Puskesmas Helvetia from December 2023 to June 2024. The population of this study consisted of all HIV-positive patients at Puskesmas Helvetia, totaling 855 individuals. A purposive sampling technique was used for case and control sampling, with a sample size of 154, split evenly between cases and controls (77 samples each). The study utilized both primary data, collected through interviews, and secondary data from the SIHA 2.1 application. The instrument used was a questionnaire. Data analysis was conducted using univariate descriptive analysis, including distribution and frequency. The results revealed that the majority of respondents were unemployed (53 individuals, 34.4%), had insufficient knowledge (80 individuals, 51.9%), had a history of sexually transmitted infections (STIs) (106 individuals, 68.8%), identified as homosexual (120 individuals, 77.9%), and did not use condoms (110 individuals, 71.4%). The low level of knowledge regarding STIs contributed to high-risk sexual behaviors, including inconsistent condom use. Therefore, there is a need for interventions such as more intensive health education, improved access to sexual health services, and economic empowerment programs for vulnerable groups to reduce STI incidence. Keywords: HIV, AIDS, Incidence